Concordance and Disconcordance of Serum Levels of Leptin with Leucocyte Telomere Length Across Spectrum of Adult Body Mass Index Among Indian Rural Population - Anurag Yadav; L G Nandakumar; Anmol Manaswini Golla Yadav; Srivats Golla Yadav; Kaveri N Karewad (Universitas Brawijaya, 2023)
Background: Obesity is a prominent avoidable cause of mortality and a growing health concern in both adults and children throughout the world. The study's goal is to measure leucocyte telomere length and its relationship with leptin throughout the BMI spectrum. Material & Method: This cross sectional study was conducted among patients attending tertiary care hospital fulfilling the inclusion criteria. The serum taken from these samples was numbered and sent to the lab in an ice box for Leptin and Telomere length analysis. Telomere length was measured in leukocytes using the qPCR method. Result: Total of 360 patients with mean age of the patients 47.84±15.84yrs, equally distributed in age group of 25-39yrs, 40-54yrs and >=55yrs of age. A significant negative strength of association of BMI with telomere length (r=-0.21, p<0.05) and a significant association of waist to hip ratio with telomere length (r=0.24, p<0.05). No significant relation between telomere length with the serum level of Leptin (r=0.09, p=0.386). Conclusion: The mean Telomere length correlated negatively with BMI and age. In the current investigation, leptin had no significant connection with telomere length.